Coaching to increase water intake in CKD 1–5: overview and detailed analysis of three clinical trials - Ivanova, Mariia D.; Gozhenko, Anatoliy I.; Crestanello, Tommy; Ivanov, Dmytro D. (KIDNEYS, 2021)
Parallel two-group prospective multicentre randomized trial named “HYD45 — Hydration in CKD 4–5 stages” that enrolled 62 patients with CKD G4–5 was aimed at evaluating of estimated glomerular filtration rate (eGFR) with coaching to increase water intake (CIWI) with the achievement of minimally higher diuresis by 400 mL in 31 patients compared with the CKD G4–5 group without CIWI. The stated duration was 12 months, and the trial was terminated in 6 months due to a more pronounced eGFR drop in the CIWI group, namely –3.3 ml vs. 2 ml in the group without CIWI. eGFR, renal functional reserve (RFR), albumin-to-creatinine ratio, and patient’s quality of life were additionally analyzed in this trial. Finally, three randomized clinical trials were analyzed in which patients with CKD 1–2, 3, and 4–5 received hydration. The results of studies demonstrate the possible efficacy of CIWI in stage 1–2 CKD in patients with normal or increased renal functional reserve. In stage 3 CKD, CIWI showed no benefits, and in stage CKD 4–5, forced hydration resulted in greater renal function loss. Summarizing these data, the authors concluded that it is probably appropriate for healthy people to consume the amount of fluid that provides physiological diuresis of 1.2–1.8 L and urine normal osmolarity. CIWI is often excessive, forced excessive hydration may not promote a healthy lifestyle. CIWI becomes forced excess hydration as kidney function decreases. Possibly, the benefits of CIWI are lost in CKD with the progression of renal function reduction. The effect of CIWI for 12 months may be positive for stage 1 CKD and stage 2 CKD with normal functional renal reserve. CIWI is probably impractical for chronic stages 3–5 CKD. In CKD 4–5, RFR is not preserved, which probably explains the negative effect of CIWI. With CKD G1, the CIWI leads to the optimal preservation of the renal function with the increase of GFR per 1 ml/min/1.73 m2 per year in comparison with the same water intake. In CKD G2, CIWI prevents physiological and pathological loss of renal function, RFR above 50 % provides restoration of eGFR in CKD G1–2. Early Coaching to Increase Water Intake in CKD (ECIWIC) trial demonstrates benefits of CIWI in patients with CKD G1–2 and preserved RFR and may be recommended to delay the CKD worsening.